2002
DOI: 10.1046/j.1365-2265.2002.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone release after glucagon as a reliable test of growth hormone assessment in adults

Abstract: The glucagon GH test is reliable and provides a clear separation between GH-deficient and normal adults. A single glucagon test with a cut-off of 3 microg/l for the GH peak is diagnostic of GH deficiency in adults and could be considered and studied as an alternative to the ITT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 28 publications
2
102
1
4
Order By: Relevance
“…Gomez et al, who evaluated the GST in healthy controls, found that none of their 46 volunteers failed to achieve a GH response !3 mg/l; however, the population used was lean. They did, however, note a significant correlation between BMI and peak GH response (30). We have demonstrated a negative correlation between peak GH and BMI in both healthy controls and in SAH patients; patients and healthy controls with a BMI O30 kg/m 2 frequently failed to achieve a peak GH level O3 mg/l.…”
Section: Discussionmentioning
confidence: 86%
“…Gomez et al, who evaluated the GST in healthy controls, found that none of their 46 volunteers failed to achieve a GH response !3 mg/l; however, the population used was lean. They did, however, note a significant correlation between BMI and peak GH response (30). We have demonstrated a negative correlation between peak GH and BMI in both healthy controls and in SAH patients; patients and healthy controls with a BMI O30 kg/m 2 frequently failed to achieve a peak GH level O3 mg/l.…”
Section: Discussionmentioning
confidence: 86%
“…Among classical provocative tests, while the diagnostic reliability of ITT has been confirmed by many studies, the glucagon test has been validated more recently showing quite good sensitivity (Se) and specificity (Sp) (16,17). On the other hand, it has been demonstrated that testing with ARG alone should not be considered a reliable alternative test (18).…”
Section: How To Testmentioning
confidence: 99%
“…41 For GHD, we utilized the glucagon stimulation test, which is a well-validated test for this purpose. 32,33,36,[42][43][44] Given that a majority of this cohort was obese and that peak GH levels are negatively correlated with BMI for all types of GH stimulation testing, including glucagon, GHRH/arginine, and the insulin tolerance tests, it was necessary to use a BMI-adjusted definition for GHD with a control cohort of overweight subjects.…”
Section: Defining Hormonal Deficiencymentioning
confidence: 99%
“…31,32 Because of this known inverse relationship with BMI and peak GH after stimulation testing with glucagon, GHRH/arginine, and insulin tolerance testing, GHD was defined at 3 cut points, adjusted for BMI using a normal non-head-injured control cohort referred to the Dynamic Endocrine Testing Unit at the Oregon Health & Science University (Portland, OR) for assessment of possible GHD with low normal to low serum IGF-1 levels. 27,[33][34][35][36] From 119 men tested, individuals were excluded if they had a previous history of pituitary or hypothalamic tumor, other hypothalamic or pituitary disorder, pituitary surgery or irradiation, or TBI. Thirty individuals from these 119 men met the criteria and made up the control group.…”
Section: Pituitary Hormonal Testingmentioning
confidence: 99%